Statistical Quality Control pada Produk Air Minum dalam Kemasan Merek X di CV XYZ - Diantami, Melati; Rosha, Media (UNIVERSITAS NEGERI PADANG, 2023)
Bottled water is one alternative that can be used to meet the clean water needs in society. X brand of bottled water is one of the brands circulating in West Sumatra. Based on the quality requirements of SNI 01-3553-2015, pH and the amound of dissolved subtances are some aspects that can cause some diseases if they do not meet the set standards. In addition, the volume of water in each package must be in accordance with what is stated on the package. This study aims to determine the quality of bottled water products using the and control charts in statistical quality control. The research sample was obtained from CV XYZ in Padang. The research instrument used measurement tools such as measuring glasses, dropper, digital pH meter and TDS meters. The results showed that all variables were not controlled based on the and control charts.